Use of Arthrospira platensis (Nordst.) Geitl for poultry waste utilization - (:unkn) unknown (К.: Фітосоціоцентр, 2013)
The possibility of Arthrospira platensis cultivation in the organic nutrient medium consisting of extracts of chicken dung has been experimentally investigated. Chicken dung, as a multi-component mixture of various chemicals, stimulates the growth of algae. It is can be used as a free raw material for microalgae cultivation.